Dynamics of changes in the breed composition of pastoral and agro-pastoral cattle herds in Benin: implications for the sustainable use of indigenous breeds. Issue 4 (April 2022) - Houessou, S.O.; Vanvanhossou, S.F.U.; Diogo, R.V.C.; Dossa, L.H.
Abstract: Data for concretely analyzing current trends regarding breed composition of cattle herds at the national scale and the logic behind it are lacking in Benin. This study aimed to investigate the factors affecting the dynamics of breed composition in traditional Beninese cattle herds. In this regard, the main reasons for acquiring new breeds by herders and management strategies for animal genetic diversity in herds were targeted. Using a semi-structured questionnaire, a total of 753 cattle herds were surveyed in six pastoral communities along a north-south transect in Benin. Data collection included original breed composition of the herds (at their installation), cattle breeds introduced in the last five years, reasons for introducing new breeds, herders' breed preferences, and perceptions concerning productive and adaptive traits of the existing breeds in the study area. Descriptive analyses of herd composition revealed breed redistribution across the country with the increasing introduction of zebu in the southern region of the country. A high percentage of nondescript crossbreeds was associated with herders' willingness to improve both milk and meat production. In this regard, the analysis of herders' perceptions using the Friedman test ranked most zebu cattle breeds as the most productive. In contrast, the taurine breeds were highly ranked by herders for their adaptive features. This study confirms that herders' breed choices fit their production objectives. In addition, strategies for effectively and efficiently managing genetic diversity within herds are expected to increase animal productivity while conserving adaptive and special traits in local breeds. The effectiveness of herders' knowledge of local cattle breeds as well as their experience may increase the success of such strategies and facilitate their adoption. Highlights: Redistribution of cattle breeds across the country. Increasing presence of Zebu in the humid and sub-humid regions. Emergence of nondescript crossbreed along the transect north-south. Increasing threat to the genetic integrity of the indigenous taurine cattle. Urgent need for sustainable management of cattle genetic resources. Abstract : Management of genetic diversity, Breed distribution, Herder perception, Crossbreeding.